On the multi-fuzzy sets - Benouarith et Feidjel, Fatiha et Djawhar (Faculty of Mathematics and Informatics Department of Mathematics - Option: Algebra and Disecrete Mathematics, 2020)
The subject of memoire is written within the framework of the extention of fuzzy sets, we study the basic concepts and characteristics of multi-fuzzy sets. Also, particular classes of this concept.
Keywords: Crisp set, Fuzzy set, Extension of fuzzy sets, Multi-fuzzy set.